Between self-promotion and self-depreciation – Joachim Lelewel’s linguistic means of self-presentation in his emigrant correspondence addressed to friends and acquaintances - Jaros, Violetta (Papers in Linguistics, 2025)
The article concerns a description of Joachim Lelewel’s ways of self-presentation in the correspondence addressed to his friends and acquaintances, which the scholar-politician wrote in exile in the years 1831–1860. Linguistic observations offered in the article refer to the sender’s ways of revealing himself (self-presentation indices) and self-presentation actions. The basic research assumption of the study is a thesis that the tendency to reveal self-presentational styles and the choice of linguistic means that refer back to the text are individual in nature.